THE PREVENTION OF SYSTEMIC LIQUIDITY RISK IN MODERN CONDITIONS OF BANKING REGULATION - Чібісова, Вікторія (Socio-economic relations in the digital society, 2019)
The urgency and danger of systemic risks of the banking sector are highlighted. The features to the interpretation of the concept of systemic risk from both the position of scientists and through the prism of international organizations dealing with issues of regulation of financial markets are determined. There are three main approaches to understanding: microeconomic, macroeconomic and integrated are written. The concept of systemic liquidity risk, features of it’s distribution and necessity of regulation are disclosed. The methods of measuring the systemic liquidity risk in accordance with international practice are indicated and the main parameters of its estimation in the domestic banking sector are presented. Complex analysis of the banking system of Ukraine was conducted to identify a systemic liquidity risk or finding the possibility of developing it, and draw some conclusions. The necessity of strengthening control over systemically important banking institutions is mentioned. The prospects for improving the regulation of systemic liquidity risk for the Ukrainian banking market are proposed.
Keywords: banking regulation; financial system; systemic risk; systemic liquidity risk; high liquid assets; refinancing; systemically important institutions